Efforts to Improve Student Learning Outcomes in Class IV Mathematics Subjects Using the Demonstration Method at SDN Banjarsari 1 - Kusmawati, Teti (Jurnal Primagraha, 2023)
This research aims to describe the increase in students' learning activities in mathematics on adding and subtracting fractions through the demonstration method. The location chosen for this research was Class IV of SD Negeri Banjarsari 1, Cipocok Jaya District, Serang City with a total of 30 students consisting of 15 male students and 15 female students. Class IV of Banjarsari 1 State Elementary School, Cipocok Jaya District, Serang City is the place of work for researchers. The research method used is demonstration. This research was carried out in two action cycles and each cycle consisted of stages of planning, action implementation, observation and reflection. The learning outcomes obtained include the average learning result score for cycle II which is 75 with the highest score being 100 and the lowest score being 40. Apart from that, the level of learning completeness in cycle II reached 80% which turned out to be higher than the classical completeness requirement of 80%. Therefore, there is no need for learning treatment in the next cycle.